Health care renunciation in Tunisian diabetic patients, 2016. (30th September 2020) - Rejaibi, S; Cherif, I; Ben Mansour, N; Zoghlami, N; Saidi, O; Skhiri, A; Ben Slama, F; Ben Romthane, H; Turki, Z; Aounallah-Skhiri, H
Abstract: Background: Diabetes management requires access to health care, patient awareness about hygiene and diet measures, and patient adherence to prescribed treatment. Health care renunciation (HCR) can make diabetes management really challenging. We aimed to determine the prevalence of HCR in diabetic Tunisian patients and assess associated factors. Methods: Data were obtained from the 2016 Tunisian Health Examination Survey, a household survey stratified at three degrees. For each household, two people aged 18 and over were randomly selected. Data were collected using: a household questionnaire and an individual questionnaire (risk behaviours and medical history). Diabetic patients were asked whether, they had renounced any health care service, the last time they needed to seek healthcare. Data analysis was performed with R software. Results: A total of 880 diabetic patients were included in this survey, with a mean age of 61±12 years and a sex ratio M/F equal to 0.9. The prevalence of HCR was 4.9% (95% CI [3.3-6.5]), higher in men (7.4% VS 2.6% in women, p = 0.003) and higher in urban areas (5.4% VS 3.1 in rural areas, p = 0.09). After multivariate adjustment (taking into consideration age, gender, profession, health insurance and place of residence as independent variables), having no health insurance and being aged more than 50, were significantly associated to HCR, with adjusted Odds Ratios equal to (3.8, 95% CI [1.4-9.2]) and (3.4, 95% CI [1.9-10.1]), respectively. Conclusions: Our study has highlighted a relatively low prevalence of HCR compared to literature data (4.9% VS 10-15%), explained mostly by methodological differences regarding HCR assessment. HCR in diabetic patients is mostly explained by economic reasons, which show how important is a better organisation of Tunisian public health system to ensure equity in access to health care. Key messages: Health care renunciation in diabetic Tunisian patients is explained mainly by financial reasons (having no health insurance). Moving further towards improving universal health coverage is a key pillar in the proper management of chronic diseases such as diabetes.